Organic silicon rubber with soft lignin as crosslinking point and preparation method of organic silicon rubber

By using softlignin as a crosslinking point and combining with hydrogen-capped polydimethylsiloxane and carbon black powder, the mechanical properties of traditional silicone rubber when using hardlignin is solved, and silicone rubber with high mechanical properties, flame retardant properties and heat resistance is achieved without the need for additional crosslinking agent.

CN119708850APending Publication Date: 2025-03-28CHENGDU GUIBAO SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411905164.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When traditional silicone rubber uses hardlignin as a crosslinking agent, it will react with end-hydrogen silicone oil and catalyst, affecting its mechanical properties, and requires additional coupling agent or crosslinking agent, which increases cost and complexity.

Method used

Cornegin is used as the crosslinking point, and by using it with hydrogen-capped polydimethylsiloxane and carbon black powder, combined with Piers-Rubinsztajn reaction, the condensation of hydrogen-capped polydimethylsiloxane and phenolic hydroxyl and methoxy groups on the surface of lignin under strong Lewis acid catalysis, forming a crosslinking structure.

Benefits of technology

Without additional coupling agent or crosslinking agent, the mechanical properties, flame retardant properties and heat resistance of the silicone rubber are improved, and the construction and mechanical properties of the material are taken into account.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708850A_ABST
    Figure CN119708850A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic silicon rubber, and discloses organic silicon rubber with soft lignin as a crosslinking point and a preparation method thereof.The organic silicon rubber comprises a component A and a component B. The mass ratio of the component A to the component B is (2-3): 1, and the component A comprises, by mass, 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin and 10 parts of carbon black powder; the component B comprises the following components in parts by weight: 100 parts of dimethyl silicone oil, 5 parts of a defoaming agent, 10 parts of a solvent and 0.08 part of a catalyst. The rubber product prepared by the technical scheme does not adopt a traditional addition type or condensation type silicone rubber cross-linking agent, but directly uses the soft lignin widely existing in the nature as a filler and a cross-linking point at the same time, and the heat resistance and flame retardance are improved to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic silicone rubber, and in particular to an organic silicone rubber with soft lignin as a cross-linking point and a preparation method thereof. Background Art

[0002] Silicone rubber is based on silicon-oxygen bonds, with a bond energy of about 460 kJ / mol. It has good weather resistance, but its own mechanical strength is not high, and it needs to be used with various fillers. Conventional reinforcing fillers are mostly inorganic substances: such as calcium carbonate, white carbon black, metal oxides, etc. Depending on the different end groups and side chain groups of polysiloxane, it can be combined with different multi-functional molecules to form an elastomer with a three-dimensional network structure.

[0003] Lignin is a complex organic substance in plants. It is the second largest biomass resource in the plant kingdom after cellulose. It is a biopolymer with a three-dimensional network structure (G type, S type, H type) formed by three phenylpropane monomers and their derivatives connected to each other through carbon-oxygen bonds and carbon-carbon bonds. The lignin formed by different types of plants has different monomer ratios, monomer connection methods and cross-linking structures. For example, G-type lignin monomers account for the majority in softwood, while G-type and S-type are the main types in hardwood. Lignin extracted from plants is a brown powder with a structure of polymer macromolecular particles. The surface of the particles has phenolic hydroxyl groups and methoxy groups. The two chemical groups determine that lignin has a certain reactivity.

[0004] CN117402407A discloses a preparation method using sodium lignin sulfonate as a silicone rubber modifier, which improves the mechanical properties and thermal stability of silicone rubber; CN109796739B discloses a technology of polymerizing silicone rubber and methyl acrylate to form a polyester elastomer, and then adding lignin to modify it, which improves the toughness, heat resistance and mechanical properties of the elastic material; CN117363209A discloses a technology of adding lignin fibers to a silicone rubber coating system. After ablation, the lignin fibers are combined with other fillers to form pore channels, so that the coating can promote uniform volatilization of the solvent and transmission of moisture in the air into the coating, further reducing the situation where the coating is unevenly cured and generates internal stress and causes cracking.

[0005] Although the above technologies use lignin and its derivatives in the silicone system, they are all used to reinforce, toughen, and improve the heat resistance and other properties of the mature silicone cross-linking system. They often require specific silane coupling agents or hydrogen-containing silicone oils as cross-linking agents. Traditional hard lignin is mostly a long-chain structure, which will react with hydrogen-terminated silicone oils and catalysts, affecting the mechanical properties of silicone rubber. Summary of the invention

[0006] The present invention aims to provide an organosilicon rubber with soft lignin as a crosslinking point and a preparation method thereof, aiming to take into account the mechanical properties, flame retardant properties and heat resistance of the organosilicon rubber without adding additional coupling agents or crosslinking agents.

[0007] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: an organic silicone rubber with soft lignin as a cross-linking point, comprising component A and component B, the mass ratio of component A to component B is 2-3:1, and in parts by mass, component A comprises: 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin, and 10 parts of carbon black powder; component B comprises: 100 parts of dimethyl silicone oil, 5 parts of a defoaming agent, 10 parts of a solvent, and 0.08 parts of a catalyst.

[0008] Preferably, as an improvement, the molecular particle size of the soft lignin is ≤65 μm.

[0009] In this technical solution, the particle size of the soft lignin has a key influence on the reaction rate. Studies have shown that too large a particle size of the soft lignin will affect the appearance of the silicone rubber, and the larger the particle size, the smaller the specific surface area, and the lower the corresponding active group concentration, which affects the reaction rate.

[0010] Preferably, as an improvement, the viscosity of the hydrogen-terminated polydimethylsiloxane at 25° C. is 5000 to 20000 mPa·s.

[0011] In the technical solution, hydrogen-terminated polydimethylsiloxane can take into account both the construction performance and mechanical properties of the material at this viscosity.

[0012] Preferably, as an improvement, the particle size of the carbon black powder is ≤20 μm.

[0013] In the technical solution, carbon black can cover the brown color of lignin itself, making the silicone rubber black to achieve universal use.

[0014] Preferably, as an improvement, the viscosity of the dimethyl silicone oil is 50 to 500 mPa·s.

[0015] In this technical solution, the addition of dimethyl silicone oil can reduce the viscosity of the system, increase the extrusion performance of silicone rubber and improve the mechanical properties of precious rubber.

[0016] Preferably, as an improvement, the defoaming agent is allyl alcohol epoxy group-terminated polyether-modified silicone oil, and the viscosity of the allyl alcohol epoxy group-terminated polyether-modified silicone oil is 350 mPa·s.

[0017] In the present technical solution, the defoaming agent can effectively control the generation and elimination of bubbles in the system (mainly methane and hydrogen), and the above-mentioned defoaming agent has good performance in the present technical solution.

[0018] Preferably, as an improvement, the solvent is one of hexane, cyclohexane and toluene.

[0019] In the present technical solution, the solvent is mainly used to dissolve the catalyst and evenly disperse it in the organosilicon oil system, so that the reaction can be more stable and uniform.

[0020] Preferably, as an improvement, the catalyst is B(C6F5)3.

[0021] In the technical scheme, the catalyst is B(C6F5)3, whose strong Lewis acidity can catalyze the reaction of Si-H with -OH or -OCH3 in lignin, while other Lewis acids, such as platinum catalysts, are easily consumed by reacting with lignin; the acidity of organotin catalysts is slightly poorer and is not enough to catalyze the reaction of lignin with terminal hydrogen silicone oil; BCl3 is easy to react with the ether bond inside lignin due to the small steric hindrance of Cl atom, causing the latter reaction.

[0022] Preferably, as an improvement, a method for preparing an organosilicon rubber with soft lignin as a cross-linking point comprises the following steps:

[0023] Step 1: Grind the soft lignin to obtain a powder with a particle size of ≤65 μm;

[0024] Step 2: Place the refined soft lignin powder and carbon black powder into a vacuum oven to remove water;

[0025] Step 3: 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin, and 10 parts of carbon black powder are stirred and mixed under -0.08 MPa to prepare component A;

[0026] Step 4, dissolving the catalyst in a solvent to obtain system I;

[0027] Step 5: Stir and mix the system I, defoamer and dimethyl silicone oil under -0.08 MPa to prepare component B;

[0028] Step 6: Mix components A and B in a mass ratio of 2 to 3:1 and cure at room temperature.

[0029] Preferably, as an improvement, in step 2, the temperature of the vacuum oven is 80° C., the pressure is -0.08 MPa, and the water removal time is 2 to 4 hours.

[0030] The principle and advantage of this solution are: in this technical solution, the Piers-Rubinsztajn reaction is used to condense the hydrogen-terminated polydimethylsiloxane with the phenolic hydroxyl group and methoxy group on the surface of lignin under the catalytic action of a strong Lewis acid.

[0031]

[0032] The principle of this reaction is that the strong Lewis acid B(C6F5)3 with an empty orbital will accept the negatively charged H of Si-H and form a three-center two-electron structure, which is connected to the hydrogen-terminated polydimethylsiloxane main chain. At this time, the positively charged Si atom center is more susceptible to attack by nucleophiles, forming oxonium ion intermediates with -OH or -OCH3 on the surface of lignin and rearranging, and finally dehydrogenation / demethanization condensation occurs.

[0033]

[0034] During the technical research and development stage, the optimization of lignin types and particle sizes is one of the difficulties of this technical solution: in addition to the surface groups, some ether bonds in the internal structure of some lignins will also be decomposed by B(C6F5)3 catalysis, resulting in structural damage; based on this, this technical solution uses soft lignin with a three-dimensional cross structure as raw material, and its internal phenylpropane monomers are mostly connected by CC bonds and will not react with terminal hydrogen silicone oil and catalysts, while hard lignin has a chain structure, and the ether bond components of the internal phenylpropane monomers are more than those of soft lignin, and are easily decomposed by terminal hydrogen silicone oil under the catalysis of B(C6F5)3 (comparison of the internal structures of hard lignin and soft lignin, for example). Fig.12 ). In addition, the above reaction will release a certain amount of gas. If the reaction speed is too slow and the gas cannot escape in time, a large number of pores will appear in the elastomer to form foam, and the required silicone rubber structure cannot be obtained. This is also one of the difficulties and viewpoints in the development of this technical solution. Based on this, this technical solution focuses on the particle size of lignin and the ratio of lignin, hydrogen-terminated polydimethylsiloxane and catalyst, aiming to achieve reasonable regulation of the reaction rate. In terms of the particle size of lignin, this technical solution limits the molecular particle size of soft lignin to ≤65μm. Lignin with too large a particle size will not only have appearance problems, but also be difficult to fully disperse in silicone rubber, and will also cause difficulty in extrusion of component A. By controlling the ratio of lignin, hydrogen-terminated polydimethylsiloxane and catalyst, it is possible to avoid the mismatch between the speed of hydrogen generation during the reaction and the speed of rubber curing, thereby avoiding the appearance of pore-like holes (and the size of this type of holes cannot be controlled) that make it impossible to use it as a foam material.

[0035] In summary, the beneficial effects of this technical solution are:

[0036] 1. In this technical solution, the three-dimensional cross-structured soft lignin is used as the raw material, and the phenylpropane monomers inside it are mostly connected by CC bonds, which will not react with the hydrogen-terminated silicone oil and the catalyst, thereby ensuring the mechanical properties of the silicone rubber material.

[0037] 2. In the prior art, lignin is added, and in most cases it is used as a reinforcing filler for rubber. However, the present technical solution creatively uses it together with hydrogen-terminated polydimethylsiloxane to synergistically exert a cross-linking effect, thereby realizing an unconventional use of lignin, obtaining unexpected technical effects, and having environmental significance.

[0038] 3. In this technical solution, neither the traditional condensation-type silicone rubber crosslinking agent (such as dealcoholization type, dealcoholization type, etc.) nor the traditional addition-type silicone rubber vinyl silicone oil is used. Instead, the silicone long chain directly reacts and combines with the filler to form a three-dimensional network structure, which greatly improves the combination efficiency of the reinforcing filler and the silicone rubber long chain.

[0039] 4. In this technical solution, by controlling the type and particle size of lignin and the ratio of lignin, hydrogen-terminated polydimethylsiloxane and catalyst, the reaction rate can be precisely controlled, thereby ensuring the mechanical, flame retardant and heat-resistant properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a cross-sectional view of the colloid prepared in Example 1 of the present invention.

[0041] Figure 2 This is a cross-sectional view of the colloid prepared in Example 2 of the present invention.

[0042] Figure 3 This is a cross-sectional view of the colloid prepared in Example 3 of the present invention.

[0043] Figure 4 This is a cross-sectional view of the colloid prepared in Comparative Example 2 of the present invention.

[0044] Figure 5 This is a cross-sectional view of the colloid prepared in Comparative Example 3 of the present invention.

[0045] Figure 6 This is a cross-sectional view of the colloid prepared in Comparative Example 4 of the present invention.

[0046] Figure 7 This is a cross-sectional view of the colloid prepared in Comparative Example 6 of the present invention.

[0047] Figure 8 This is a cross-sectional view of the colloid prepared in Comparative Example 7 of the present invention.

[0048] Fig. 9 This is a cross-sectional view of the colloid prepared in Comparative Example 8 of the present invention.

[0049] Fig.10 This is a cross-sectional view of the colloid prepared in Comparative Example 9 of the present invention.

[0050] Fig.11This is a cross-sectional view of the colloid prepared in Comparative Example 10 of the present invention.

[0051] Fig.12 Comparison of the internal structures of hard lignin (left) and soft lignin (right). DETAILED DESCRIPTION

[0052] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0053] A silicone rubber with soft lignin as a crosslinking point comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 2-3:1. In parts by mass, the component A comprises: 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin, and 10 parts of carbon black powder; the component B comprises: 100 parts of dimethyl silicone oil, 5 parts of a defoaming agent, 10 parts of a solvent, and 0.08 parts of a catalyst.

[0054] The viscosity of hydrogen-terminated polydimethylsiloxane at 25° C. is 5000 to 20000 mPa·s.

[0055] The molecular particle size of soft lignin is ≤65μm.

[0056] The particle size of carbon black powder is ≤20μm.

[0057] The viscosity of dimethyl silicone oil is 50 to 500 mPa·s.

[0058] The defoaming agent is allyl alcohol epoxy-terminated polyether modified silicone oil, and its viscosity is 350 mPa·s.

[0059] The solvent is one of hexane, cyclohexane and toluene.

[0060] The catalyst is B(C6F5)3.

[0061] A method for preparing an organosilicon rubber with soft lignin as a cross-linking point comprises the following steps:

[0062] Step 1: Refine the soft lignin powder in a high-speed planetary ball mill at a revolution speed of 200 rpm and a rotation speed of 1200 rpm, and then filter out the powder with a size greater than 65 μm with a sieve;

[0063] Step 2: Place the refined soft lignin powder and carbon black powder in a vacuum oven at 80°C and -0.08MPa to remove water for 2 to 4 hours;

[0064] Step 3: Add 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin, and 10 parts of carbon black powder into a planetary mixer, and stir and mix at a speed of 200 rpm for 30 minutes under a vacuum condition of -0.08 MPa to prepare component A;

[0065] Step 4, dissolving the catalyst in a solvent to obtain system I;

[0066] Step 5: Add system I, defoamer and dimethyl silicone oil into a planetary mixer in proportion, and stir and mix at a speed of 120 rpm for 15 minutes under a vacuum condition of -0.08 MPa to prepare component B;

[0067] Step 6: Mix components A and B in proportion, then cure at room temperature for 24 hours, and maintain under standard conditions (23° C., 55% humidity) for 7 days for subsequent use and testing.

[0068] Examples and Comparative Examples

[0069] According to the preparation process summarized in the above scheme, silicone rubber with the following formula was prepared. The raw material composition of each embodiment and comparative example is shown in Table 1:

[0070] Table 1

[0071]

[0072]

[0073] *: The particle size of the soft lignin in this comparative example is 70 μm

[0074] The silicone rubber of the above embodiments and comparative examples was subjected to performance tests, and the test indicators, test methods and test results are shown in Table 2:

[0075] Table 2

[0076]

[0077]

[0078] From the data in Table 2, it can be seen that although the formulations of the three examples have differences in the allowable range of lignin content and AB component ratio, the final performance is basically similar, indicating that the silicone rubber prepared by the present invention has good mechanical properties, suitable operability time, and both heat resistance and flame retardant effects, and the final rubber structure is a dense elastomer (see Appendix Figure 1 , 2 , 3).

[0079] By comparing the data of comparative example 1 with those of the embodiment, the mechanical properties, heat resistance and flame retardancy of the silicone rubber cross-linked by soft lignin are significantly improved compared with the mainstream two-component addition silicone rubber. This is mainly because the polysiloxane molecules of the embodiment are directly connected to the filler through chemical bonds, and the flame retardancy and heat resistance of the lignin molecules themselves are also better than those of fumed silica, and the thickening effect of lignin is weaker than that of silica, so more powder can be added to the same amount of silicone rubber;

[0080] By comparing the data of Comparative Example 2 with those of the embodiment, when using hard lignin and soft lignin respectively, the mechanical properties and heat resistance of the silicone rubber made of hard lignin are poor, and it basically has no flame retardant properties, and the hardness is also lower. This is mainly because the structure of hard lignin is more long-chain, without cross-linking and reinforcement effects, and the monomers are connected by the CO bond of phenolic hydroxyl groups, which is easily decomposed by B(C6F5)3 catalysis, and cannot form a strong three-dimensional cross-linked structure (see Appendix Figure 4 ) and therefore have little strength;

[0081] By comparing the data of comparative example 3 with those of the embodiment, when BCl3 is used as a catalyst, the mechanical properties and flame retardant effect of the silicone rubber using soft lignin as a crosslinking system are worse. This indicates that due to the smaller steric hindrance of BCl3, it can catalyze the reaction of the CO bond inside the soft lignin with the hydrogen-terminated polydimethylsiloxane, causing the destruction of the internal structure (see attached Figure 5 ), and because of its stronger activity, the operating time of silicone rubber is greatly shortened;

[0082] By comparing the data of Comparative Example 4 with those of the embodiment, it is found that without adding allyl alcohol epoxy-terminated polyether-modified silicone oil as a defoamer, the H2 and CH4 generated by the crosslinking reaction cannot be eliminated in time, thus leaving a large number of bubble cavities during the rubber curing process (see attached figure). Figure 6 ), resulting in mechanical properties not as good as those of the embodiment, but since the cross-linked structure of soft lignin-hydrogen-terminated polydimethylsiloxane is basically formed, it still has certain heat resistance and flame retardant properties;

[0083] Comparative Example 5 shows that the conventional platinum catalyst + inhibitor system cannot catalyze the reaction between soft lignin and hydrogen-terminated polydimethylsiloxane. Since the platinum catalyst has a coordinated empty orbital like B(C6F5)3, the possible reason for this phenomenon is that the soft lignin itself or trace impurities cause the platinum catalyst to be "poisoned";

[0084] By comparing the data of Comparative Example 6 with those of the embodiment, when the mixing ratio of the AB components reaches 1:1, the relative content of the catalyst is significantly increased, the operable time is significantly shortened, and the generated bubbles are solidified without being completely eliminated, thus forming certain cavities (see Appendix Figure 7 );

[0085] By comparing the data of comparative example 7 with those of the embodiment, when the mixing ratio of components AB reaches 5:1, the relative content of the catalyst is significantly reduced, the operable time is significantly prolonged, and it takes a considerable amount of time to fully cure. However, the final rubber has a good structure (see attached Figure 8 ) and performance, there is no significant difference from the embodiment;

[0086] By comparing the data of comparative example 8 with those of the embodiment, when the particle size of the softwood lignin is too large (70 μm), the specific surface area is correspondingly reduced, and the reinforcement effect is significantly worsened. Although the heat resistance and flame retardant effects are still there, the mechanical properties are significantly attenuated, and there are some particles in the appearance (see attached Fig. 9 );

[0087] By comparing the data of Comparative Example 9 with those of the examples, when the content of soft lignin is greatly reduced, the cross-linking and curing of the colloid is slowed down due to the reduction of the reactive groups, the operable time is greatly extended, and the overall reinforcement effect and flame retardant effect of the rubber are significantly attenuated, although the appearance of the rubber is still a dense elastomer (see attached Fig.10 );

[0088] By comparing the data of comparative example 10 with those of the embodiment, when the content of soft lignin is greatly increased, there are too many reactive groups, the colloid cross-links too quickly, the operating time is greatly shortened, and the generated gas cannot be discharged in time, forming a porous foam structure (see attached Fig.11 ), the overall reinforcement effect of the rubber is significantly weakened.

[0089] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. An organic silicone rubber with soft lignin as crosslinking point, characterized in that: The invention comprises component A and component B, wherein the mass ratio of component A to component B is 2-3:

1. In parts by mass, component A comprises: 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin, and 10 parts of carbon black powder; component B comprises: 100 parts of dimethyl silicone oil, 5 parts of defoaming agent, 10 parts of solvent, and 0.08 parts of catalyst.

2. The organic silicone rubber with soft lignin as crosslinking points according to claim 1, characterized in that: The molecular particle size of soft lignin is ≤65μm.

3. The organic silicone rubber with soft lignin as crosslinking points according to claim 2, characterized in that: The viscosity of hydrogen-terminated polydimethylsiloxane at 25° C. is 5000 to 20000 mPa·s.

4. The organic silicone rubber with soft lignin as crosslinking points according to claim 3, characterized in that: The particle size of carbon black powder is ≤20μm.

5. The organic silicone rubber with soft lignin as cross-linking points according to claim 4, characterized in that: The viscosity of dimethyl silicone oil is 50 to 500 mPa·s.

6. The organic silicone rubber with soft lignin as crosslinking points according to claim 5, characterized in that: The defoaming agent is allyl alcohol epoxy group-terminated polyether-modified silicone oil, and the viscosity of the allyl alcohol epoxy group-terminated polyether-modified silicone oil is 350 mPa·s.

7. The organic silicone rubber with soft lignin as crosslinking points according to claim 6, characterized in that: The solvent is one of hexane, cyclohexane and toluene.

8. The organic silicone rubber with soft lignin as cross-linking points according to claim 7, characterized in that: The catalyst is B(C6F5)3.

9. A method for preparing an organosilicon rubber with soft lignin as crosslinking points according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Grind the soft lignin to obtain a powder with a particle size of ≤65 μm; Step 2: Place the refined soft lignin powder and carbon black powder into a vacuum oven to remove water; Step 3: 100 parts of hydrogen-terminated polydimethylsiloxane, 30-60 parts of soft lignin, and 10 parts of carbon black powder are stirred and mixed under -0.08 MPa to prepare component A; Step 4, dissolving the catalyst in a solvent to obtain system I; Step 5: Stir and mix the system I, defoamer and dimethyl silicone oil under -0.08 MPa to prepare component B; Step 6: Mix components A and B in a mass ratio of 2 to 3:1 and cure at room temperature.

10. The method for preparing an organosilicon rubber with soft lignin as crosslinking point according to claim 9, characterized in that: In step 2, the temperature of the vacuum oven is 80° C., the pressure is -0.08 MPa, and the water removal time is 2 to 4 hours.

Citation Information

Patent Citations

  • An elastomeric polyester material and its preparation method

    CN109796739B

  • Ablation-resistant coating and application thereof

    CN117363209A

  • Silicone rubber using sodium lignin sulfonate as modifier and preparation method thereof

    CN117402407A